2011
DOI: 10.1016/j.cattod.2010.10.080
|View full text |Cite
|
Sign up to set email alerts
|

A study of the ammonia selectivity on Pt/BaO/Al2O3 model catalyst during the NOx storage and reduction process

Abstract: The ammonia selectivity during the cycling NOx storage reduction process over a model Pt/Ba/Al2O3 catalyst was studied. Firstly, it was demonstrated that, whereas the presence of water or carbon dioxide in the gas mixture have a negative effect on the storage step, the effect of these components have different impacts on the NOx efficiency. Due to their involvement in the reverse water gas shift (RWGS) reaction, the absence of water in the gas mixture leads to a drop of the NOx removal whereas without CO2, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 37 publications
1
38
1
Order By: Relevance
“…Manganese is also found to be an effective additive for Ba-based LNT catalysts. Le Phuc et al [10][11][12] found that Mn addition to Pt/Ba/Al improved NO x storage capacity and led to an improvement of NO x reduction (conversion and selectivity to N 2 ) at 400 • C. Xiao et al [13] found that Mn/Ba/Al exhibited http://dx.doi.org/10.1016/j.apcatb.2014. 10.001 0926-3373/© 2014 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese is also found to be an effective additive for Ba-based LNT catalysts. Le Phuc et al [10][11][12] found that Mn addition to Pt/Ba/Al improved NO x storage capacity and led to an improvement of NO x reduction (conversion and selectivity to N 2 ) at 400 • C. Xiao et al [13] found that Mn/Ba/Al exhibited http://dx.doi.org/10.1016/j.apcatb.2014. 10.001 0926-3373/© 2014 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In a common NSR catalyst, Pt/BaO/Al 2 O 3 , NO is oxidized to NO 2 on Pt and subsequently adsorbed on BaO as a nitrate species in the lean-burn period. Selective catalytic reduction of NO x with NH 3 has been demonstrated to be effective for power plant exhaust gas, while NO x storage reduction (NSR) technology is a promising method to eliminate NO x from diesel vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…), the H 2 consumption peak shifted to higher temperatures when NO x storage was performed in the presence of H 2 O and CO 2 . According to work by Courtois et al, reduction of CO 2 (from carbonate) via the RWGS reaction generates CO which is less efficient for the NO x reduction than H 2 , resulting in higher reduction temperatures[41]. Notably, there was no NO x release observed during the H 2 -TPSR process on Pt/Ba/Al and Pd/Co/Ba/Al.…”
mentioning
confidence: 99%